Materiali per il secondo volume della Introduzione alle scienze dello spirito: Scritti inediti 1880-1893 Drafts for Volume II of the Introduction to the Human Sciences: Unpublished Writings (1880-1893) - Wilhelm Dilthey (Scuola delle Scienze Umane e Sociali. Quaderni, 2017)
As is well-known to the scholars of European philosophical thinking between the eighteenth and twentieth centuries, the great and ambitious plan of diltheyan criticism of the reason of history condensed in a pond-pink Introduction to the Human Sciences appeared in 1883 only the first volume especially the first two Books. The volume, which we present here, encloses in chronological order the various drafts which, as early as 1880, Dilthey made the work of the second volume of the work, which would have to contain the other four Books, the dedicated ones to the gnoseological, logical and methodological aspects of the philosophical foundation of the so-called sciences of the spirit. An absorbing commitment, which Dilthey will pursue throughout his scientific life, without saving power, will cost him a little in terms of psycho-physical health. In addition to the volume, which besides Breslau drafts also contains the famous Berlin Plan dating back to the early nineties, we also thought it appropriate to include the two dafts of the "Althoff Letter" dating back to mid-1882, as they also contain useful observations on the designed Introduction to the Human Sciences.